2008
DOI: 10.1002/marc.200800055
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Method for Adjusting Thermoresponsivity: Synthesis and ‘Click’ Reaction of an Azido End‐Functionalized Poly(N‐isopropylacrylamide)

Abstract: The 2‐chloropropionamide derivative featuring an azido group is used as the initiator for the ATRP of N‐isopropylacrylamide (NIPAM) with copper(I) chloride (CuCl) and tris[2‐(dimethylamino)ethyl]amine (Me6TREN) to produce the PNIPAM end‐functionalized with an azido group. Subsequently, the ‘click’ reaction between the azido end‐group and acetylene derivatives is demonstrated to produce PNIPAM in which the end‐groups are modified by the phenyl, 4‐phenoxyphenyl, butyl, octyl, carboxylic acid, and hydroxymethyl g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 29 publications
4
99
0
Order By: Relevance
“…These results indicated that hydrophobic end-groups decreased T cp s while hydrophilic end-groups tended to increase them, and the magnitude of the effect was depended on the nature of the endgroup. Similar phenomena have been reported by Kakuchi and coworkers [22]. The end-group effect, however, is less remarkable for longer chains.…”
Section: Thermoresponsivity Of Pnipams Before and After Click Reactionsupporting
confidence: 89%
See 4 more Smart Citations
“…These results indicated that hydrophobic end-groups decreased T cp s while hydrophilic end-groups tended to increase them, and the magnitude of the effect was depended on the nature of the endgroup. Similar phenomena have been reported by Kakuchi and coworkers [22]. The end-group effect, however, is less remarkable for longer chains.…”
Section: Thermoresponsivity Of Pnipams Before and After Click Reactionsupporting
confidence: 89%
“…As shown in Figure 4, small, but clearly discernible, signals at 8.16, 7.76, 7.54, 7.46 ppm are present in the inset spectrum, corresponding to the proton of 1,2,3-triazole ring and the phenyl protons adjacent to triazole ring. Additionally, signals at 5.32, 4.54, and 4.39 ppm corresponding to the methylene protons adjacent to triazole ring as well as ester group, respectively, are also observed [22]. Further evidence for the formation of triazole can be found in the FTIR spectra ( Figure 5), by monitoring the disappearance of absorption band at 2120 cm À1 , which indicates the complete consumption of alkyne end-groups.…”
Section: Click Reactionmentioning
confidence: 83%
See 3 more Smart Citations